Fostering innovation in start-ups: The role of knowledge sharing and organizational creativity - Nony Kezia Marchyta; Eddy Madiono Sutanto; Robert Djohari (Faculty of Economics and Business, University of Muhammadiyah Malang, 2025)
The purpose was to determine the effect of knowledge-sharing on organizational innovation through organizational creativity as an intervening variable in start-up companies in Surabaya, Indonesia. The type of this data was quantitative. The sampling technique was purposive sampling, which comprised 64 start-up companies in Surabaya, Indonesia. The data were obtained through a questionnaire using a Likert scale. The data processing technique used is Partial Least Square (PLS). This study shows that knowledge-sharing affects organizational creativity and innovation at start-ups. Open communication and a culture of ongoing learning are essential to build trust and promote the free exchange of ideas. A supportive environment encourages organizational creativity, which drives the creation of novel goods and services. Continuous learning and strategically using technology are essential for innovation. Developing unique value products and rewarding creative ideas can enhance product and process innovation to achieve competitive advantage. The originality of this research was found in data collection, which considered knowledge-sharing from horizontal relationships and vertical relationships through the perspective of leaders of start-up companies.